Does Total Gastrectomy Provide Better Outcomes than Distal Subtotal Gastrectomy for Distal Gastric Cancer? A Systematic Review and Meta-Analysis. - Jin Qi; Peng Zhang; Yanan Wang; Hao Chen; Yumin Li (PLoS ONE, 2016)
Background/aims Total gastrectomy (TG) has shown to be superior regarding low risk of recurrence and readmission to distal subtotal gastrectomy (DG) for treatment of distal stomach cancer, but the incidence of postoperative morbidity and mortality in TG cannot be ignored. Therefore, we performed a meta-analysis to compare the effectiveness between TG and DG for distal stomach cancer. Methodology A search in PubMed, EMBASE, the Cochrane Library, Web of Science, Chinese Biomedical Database through January 2016 was performed. Eligible studies in comparing of TG and DG for distal gastric cancer were included in this meta-analysis. Review Manager 5.2 software from the Cochrane Collaboration was used for the performance of meta-analysis and STATA 12.0 software for meta-regression analysis. Results Ten retrospective cohort studies and one randomized control trial involving 5447 patients were included. The meta-analysis showed no significant difference of postoperative mortality (RR = 1.48, 95%CI = 0. 90-2.44,p = 0.12), intraoperative blood loss (MD = 24.34, 95%CI = -3.31-51.99, p = 0.08) and length of hospital stay(MD = 0.76, 95%CI:-0.26-1.79, p = 0.15). TG procedure could retrieve more lymph nodes than DG(MD = 4.33, 95% CI = 2.34-6.31, p<0.0001). According to different postoperative complications, we performed subgroup analysis, subgroup analysis revealed that patients in TG group tended to have a higher rate of postoperative intra-abdominal abscess than DG procedure (RR = 3.41, 95% CI = 1.21-9.63,p<0.05). No statistical differences were found in leakage, intestinal obstruction, postoperative bleeding, anastomotic stricture and wound infection between the two groups (p>0.05). We pooled the data together, the accumulated 5-year Overall Survival rates of TG and DG groups were 49.6% (919/1852) vs.55.9%(721/1290) respectively. Meta-analysis revealed a favoring trend to DG procedure and there was a statistical difference between the two groups (RR = 0.91,95% CI = 0.85-0.97,p = 0.006). Conclusion Based on current retrospective evidences, we found that in spite of similar postoperative mortality, TG for distal gastric cancer provided a high risk of five-year Overall Survival rate. DG procedure can be a recommendation for distal gastric cancer, whereas due to lack of high quality RCTs in multicenter and the relatively small sample size of long-term outcomes, further comparative studies are still needed.